Acaricides containing zein nanoparticles: A tool for a lower impact control of the cattle tick Rhipicephalus microplus - Figueiredo, Amanda [UNESP]; Anholeto, Luís Adriano; Cola, Diego Faria [UNESP]; Fantatto, Rafaela Regina [UNESP]; Gainza, Yousmel Alemán [UNESP]; dos Santos, Isabella Barbosa [UNESP]; Viçozzi, Gabriel Pedroso; Ávila, Daiana Silva; Fraceto, Leonardo Fernandes [UNESP]; Chagas, Ana Carolina de Souza (Elsevier, 2023)
Nanoformulations containing zein nanoparticles (ZN) can promote the stability and protection of molecules with acaricidal activity. The present study sought to develop nanoformulations with ZN associated with cypermethrin (CYPE) + chlorpyrifos (CHLO) + a plant compound (citral, menthol or limonene), characterize them, and verify their efficacy against Rhipicephalus microplus ticks. Additionally, we aimed to assess its safety in nontarget nematodes found in soil at a site subjected to contamination by acaricides. The nanoformulations were characterized by dynamic light scattering and nanoparticle tracking analysis. Nanoformulations 1 (ZN+CYPE+CHLO+citral), 2 (ZN+CYPE+CHLO+menthol), and 3 (ZN+CYPE+CHLO+limonene) were measured for diameter, polydispersion, zeta potential, concentration, and encapsulation efficiency. Nanoformulations 1, 2, and 3 were evaluated in a range from 0.004 to 0.466 mg/mL on R. microplus larvae and caused mortality > 80% at concentrations above 0.029 mg/mL. The commercial acaricide Colosso® (CYPE 15 g + CHLO 25 g + citronellal 1 g) was evaluated also from 0.004 to 0.512 mg/mL and resulted in 71.9% larval mortality at 0.064 mg/mL. Formulations 1, 2, and 3 at 0.466 mg/mL showed acaricidal efficacy of 50.2%, 40.5%, and 60.1% on engorged females, respectively, while Colosso® at 0.512 mg/mL obtained only 39.4%. The nanoformulations exhibited long residual period of activity and lower toxicity to nontarget nematodes. ZN was able to protect the active compounds against degradation during the storage period. Thus, ZN can be an alternative for the development of new acaricidal formulations using lower concentrations of active compounds.
Keywords: Acaricide residues; Nanocarrier; Nanoformulations; Resistance; Tick control